2021
DOI: 10.36366/frontiers.v33i1.497
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating an Intensive Program to Increase Cultural Intelligence: A Quasi-Experimental Design

Abstract: This study used a quasi-experimental design to compare the effects of an intercultural development program on students' Cultural Intelligence (CQ) compared with students in a summer research program who did not receive the intervention. Social Learning Theory guided a 9-week student-centered cultural learning course focused on attention, retention, and reproduction of each CQ domain. After the course, students had opportunities to practice their CQ abilities while studying abroad. Pre-assessment CQ determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
(67 reference statements)
2
3
0
Order By: Relevance
“…We found that a combined cultural development course and short-term study abroad experience can have a significant impact on students' CQ development in all four CQ domains. Our results are consistent with the two previous studies (Chang Alexander et al, 2021;Engle & Crowne, 2014). Our study extends upon this previous work by examining various short-term study abroad program lengths and CQ growth.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found that a combined cultural development course and short-term study abroad experience can have a significant impact on students' CQ development in all four CQ domains. Our results are consistent with the two previous studies (Chang Alexander et al, 2021;Engle & Crowne, 2014). Our study extends upon this previous work by examining various short-term study abroad program lengths and CQ growth.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies suggest metacognitive CQ may be linked to cultural contact experiences (Chang Alexander et al, 2021;Engle & Crowne, 2013;Li et al, 2013;Reichard et al, 2015;Shokef & Erez, 2008;Taras et al, 2013;Varela & Gatlin-Watts, 2014;Wood & St. Peters, 2013) such as those encountered while studying abroad. According to Varela and Gatlin-Watts (2014), shorter program length and smaller cultural distance between home country and the study abroad location appeared to moderate the effects of metacognitive CQ growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lowest value obtained for the cognitive dimension, confirmed in other studies [49][50][51][52], should serve as a guideline in the development of strategies to promote CQ in higher education institutions.…”
Section: Level Of Cqsupporting
confidence: 68%
“…However, it was confirmed that the dimension with the lowest value was cognitive. In another study with students from New Zealand, Australia and Japan, Alexander et al [52] confirmed these results.…”
Section: Cultural Intelligence In Higher Education Institutionsmentioning
confidence: 77%